Наблюдение резонансного рентгеновского переходного излучения 900 МэВ электронов в слоистой мишени - Воробьев С. А. Сергей Александрович; Забаев В. Н. Виктор Николаевич; Каплин А. А.; Калинин Б. Н.; Потылицын А. П. Александр Петрович; Розум Е. И.; Углов С. Р. Сергей Романович (1991, 1991)
Заглавие с экрана